Embolisation of an iatrogenic pulmonary artery pseudoaneurysm. (29th October 2015) - Petersen, Matthew G; Brinegar, Katelyn; Oklu, Rahmi
Abstract : A 62-year-old woman with idiopathic cardiomyopathy and class IIIB/stage C heart failure sustained right pulmonary artery injury from a Swan-Ganz catheter during a pretransplant work up. Postprocedure, it was noted that the patient's segmental pulmonary artery catheter was wedged for an unclear period of time. The patient developed a small volume of blood-tinged sputum and a chest CT revealed a 1.3 cm pseudoaneurysm in the right middle lobe medial segment pulmonary artery and a small area of haemorrhage. The patient underwent pulmonary artery preserving coil embolisation of the pseudoaneurysm to prevent further right heart strain, given an ejection fraction of 20%, which resolved haemoptysis. Imaging studies showed preserved distal outflow and no evidence of residual pseudoaneurysm filling.